2019
DOI: 10.3389/fendo.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

The Sex-Specific Detrimental Effect of Diabetes and Gender-Related Factors on Pre-admission Medication Adherence Among Patients Hospitalized for Ischemic Heart Disease: Insights From EVA Study

Abstract: Background: Sex and gender-related factors have been under-investigated as relevant determinants of health outcomes across non-communicable chronic diseases. Poor medication adherence results in adverse clinical outcomes and sex differences have been reported among patients at high cardiovascular risk, such as diabetics. The effect of diabetes and gender-related factors on medication adherence among women and men at high risk for ischemic heart disease (IHD) has not yet been fully investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Biological sex and gender-related (i.e., psycho-socio-cultural) factors play an important role as health determinants. Despite their importance, however, both aspects are generally overlooked and underreported [11][12][13][14][15][16]. Specifically, gender represents a complex construct, which includes the behavioral, cultural, environmental, and social characteristics of the individual [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…Biological sex and gender-related (i.e., psycho-socio-cultural) factors play an important role as health determinants. Despite their importance, however, both aspects are generally overlooked and underreported [11][12][13][14][15][16]. Specifically, gender represents a complex construct, which includes the behavioral, cultural, environmental, and social characteristics of the individual [11,17].…”
Section: Introductionmentioning
confidence: 99%
“…In the future, more studies are required to investigate the underlying physiological changes in women with AMI. In addition, the literature indicates that women have poorer medication adherence after MI than men, 23 and similar findings have been reported in the medical treatment of hyperlipidemia 24 and diabetes mellitus 25 . On the assessment and treatment of cardiovascular risk factors, compared with men, women, especially younger women, reported receiving less according to the guideline‐recommend management 24,26 .…”
Section: Discussionmentioning
confidence: 58%
“…In addition, the literature indicates that women have poorer medication adherence after MI than men, 23 and similar findings have been reported in the medical treatment of hyperlipidemia 24 and diabetes mellitus. 25 On the assessment and treatment of cardiovascular risk factors, compared with men, women, especially younger women, reported receiving less according to the guideline-recommend management. 24,26 Therefore, the underestimation and even improper treatment of women's CV risk might be another underlying reason for the poor long-term prognosis of women with AMI.…”
Section: Characteristicsmentioning
confidence: 99%
“…In another study, the results showed that there were no differences in sex between medium-high-compliant and low-compliant subjects. The sex-stratified analysis demonstrated that low-compliant men were more likely to be employed ( 30 ). In another study, no significant sex differences were observed ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%